Optimasi Jaringan Backbone Multiprotocol Label Switching (MPLS) Menggunakan Routing Protocol EIGRP (Studi Kasus PT. Chevron Pasifik Indonesia) - Rifaldo, Rifaldo; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Process of sending and receiving data is often a problem in telecommunications networks. Some problems such as the process of sending and receiving data require a long time, thus affecting the quality of services provided. One factor that causes service quality to be less good is the use of routing protocols. The routing protocol used has not yet supported the process of delivering highspeed packets. This study uses a Multiprotocol Label Switching (MPLS) based backbone network and the Enhanced Interior Gateway Routing Protocol (EIGRP) protocol as a packet delivery technology on high-speed backbone networks, MPLS combines several advantages of circuit-switched and packet-switched communication systems that make technology better. The software used is Graphical Network Simulator (GNS3) as a tool to design and simulate MPLS-based backbone networks at PT. Chevron Pacific Indonesia. The result shows MPLS delay from testing the data packet delivery in the form of video streaming is 31.49 ms smaller than the result of testing Non-MPLS delay which is 60.24 ms. In conclusion, MPLS can be implemented in the PT Chevron Pacific Indonesia network because the delay value obtained is smaller than the ITU standard of 150 ms. Keywords: Backbone, MPLS,EIGRP, Delay.